INVESTIGATION OF THE MATHEMATICAL MODEL OF OPTICAL FIBER - PEDYASH, Volodymyr (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Fiber optic transmission systems are the main type of systems for building telecommunication networks. The transponders of modern optical transmission systems implement efficient modulation and coding methods, which can significantly increase the receiver sensitivity and increase the length of the regeneration area. The task to define the quality characteristics of optical channels occurs during the design of such systems. To solve this problem, it is necessary to develop a mathematical model of the transmission system and perform a simulation using it. One of the main blocks of the system is the propagation medium (optical fiber). The optical fiber model is based on the nonlinear Schrödinger differential equation. Several groups of modeling methods have been developed on its basis. The most widespread is the Fourier method of splitting by physical factors, as it has a simple algorithm structure, high computing speed, and high accuracy. This method is recursive, so to reduce the number of iterations, it is reasonable to use the well-known method of nonlinear phase rotation. To check the functionality of the developed program code, it is recommended to perform testing in several stages. At the first stage, it is proposed to check the accuracy of the distortion of chromatic dispersion. Single pulses of simple shape, such as Gaussian pulses, should be used as a test signal. By calculating the pulse shape using theoretical expressions and comparing them with the modeling results, the accuracy of the optical fiber modeling algorithm can be verified. The next step in verifying the fiber model is to evaluate the accuracy of the simultaneous introduction of dispersion and nonlinear distortions. For this purpose, it is proposed to analyze the propagation of pulses of optical solitons of the first and higher orders.